Application Of Sanyinjiao And Hegu Point Acupressure For Young Women With Primary Dysmenorrhea - Refi Rizki Apriana; Arlyana Hikmanti; Fauziah Hanum Nur Adriyani (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Dysmenorrhea is abdominal pain or cramps that occur during menstruation. Characteristics of dysmenorrhea include lower abdominal pain to the waist, dizziness, nausea and fainting. In Indonesia, 64.25% of women of childbearing age experience dysmenorrhea, of which 54.89% experience primary dysmenorrhea. In Central Java, as many as 1,465,876 adolescents experience dysmenorrhea. The problem that occurs in Banyumas, to be precise the Muhammadiyah Princess Orphanage in Purwokerto, there are 19 adolescents with dysmenorrhea out of a total of 40 young women and have never received acupressure therapy with a combination of sanyinjiao and hegu points. This case study aims to carry out reproductive health care regarding a combination of acupressure therapy at sanyinjiao and hegu points to reduce the intensity of dysmenorrhea pain. The methods used were anamnesis, physical examination, Hb examination, observation at the second and third meetings, interviews and documentation studies. The target audience was selected, 5 young women from the Muhammadiyah Purwokerto Orphanage who experienced mild and moderate dysmenorrhea pain who did not do other therapy. The results of applying sanyinjiao and hegu point acupressure to reducing dysmenorrhea pain are decreasing the intensity of menstrual pain on an average scale of 1-2 and increasing the skills of young women in dealing with mild to moderate dysmenorrhea independently. Based on the results of the study, it is hoped that the respondents can apply the acupressure that has been given and can be used as a way to reduce menstrual pain when menstruation comes.